1990
DOI: 10.1128/aem.56.2.370-376.1990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth temperature and strictly anaerobic recovery on the survival of Listeria monocytogenes during pasteurization

Abstract: Listeria monocytogenes F5069 was suspended in either Trypticase soy broth-.6% yeast extract (TSBYE) or sterile, whole milk and heated at 62.8°C in sealed thermal death time tubes. Severely heat-injured cells were recovered in TSBYE within sealed thermal death time tubes because of the formation of reduced conditions in the depths of the TSBYE. Also, the use of strictly anaerobic Hungate techniques significantly increased recovery in TSBYE containing 1.5% agar compared with aerobically incubated controls. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 49 publications
9
83
3
Order By: Relevance
“…If stress occurs during growth, such as low pH, starvation, low water activity or high temperature, vegetative cells or their spores can become more, or less, heat resistant. This has been shown for a number of bacteria, such as Listeria monocytogenes (Bunning et al 1982;Knabel et al 1990;Farber et al 1992), Salmonella (Garibaldi et al 1969;Mackey and Derrick 1986), Escherichia coli (Yamamori and Yura 1982) and Bacillus subsp. (Harnulv and Snygg 1972;Wilkinson and Davies 1973;Palop et al 1996;Periago et al 1998;Palop et al 1999).…”
Section: Strains and Culture Conditionsmentioning
confidence: 72%
“…If stress occurs during growth, such as low pH, starvation, low water activity or high temperature, vegetative cells or their spores can become more, or less, heat resistant. This has been shown for a number of bacteria, such as Listeria monocytogenes (Bunning et al 1982;Knabel et al 1990;Farber et al 1992), Salmonella (Garibaldi et al 1969;Mackey and Derrick 1986), Escherichia coli (Yamamori and Yura 1982) and Bacillus subsp. (Harnulv and Snygg 1972;Wilkinson and Davies 1973;Palop et al 1996;Periago et al 1998;Palop et al 1999).…”
Section: Strains and Culture Conditionsmentioning
confidence: 72%
“…An important recent finding has been the enhanced recovery of sublethally heatdamaged cells of facultatively anaerobic organisms in anaerobic conditions. Studies with Escherichia coli O157:H7 (Mur-ano andPierson 1992, 1993), E. coli (Gadzella and Ingham 1994), Salmonella enteritidis (Xavier and Ingham 1993), Listeria monocytogenes (Knabel et al 1990;Linton et al 1992;Mendonca and Knabel 1994;Knabel and Thielen 1995;Patel et al 1995) and Staphylococcus aureus (Ugborogho and Ingham 1994), have all shown a significantly greater recovery in anaerobic than in aerobic conditions. The method of producing anaerobic conditions in these studies varied and included anaerobic overlays, addition of oxygen scavengers, incubation of plates in anaerobic jars, and preparation of media using strictly anaerobic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The increased heat resistance of cells of L. monocytogenes under anaerobic conditions may explain why a minimal heat treatment had only a marginal effect on L. monocytogenes inoculated into chicken gravy (Huang et al 1992) and sous-vide chicken breast (Shamsuzzaman et al 1992). Listeria monocytogenes also appeared to survive pasteurization at 62·8°C for 15 min when recovered anaerobically (Knabel et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…L. monocytogenes (1273) has been found to survive LTLT pasteurization and even HTST pasteurization (Knabel et al 1990;Bunning et al 1992;Doyle et al 1997). In this study the L. monocytogenes (1273) strain did not survive pasteurization at 63°C for 30 min and could not be detected after 15 min at the 1 × 10 4 cfu mL −1 inoculum and after 20 min at the 1 × 10 6 cfu mL −1 inoculum level (Tables 3 and 4).…”
Section: Reference Culturesmentioning
confidence: 61%